Evolution and state‐of‐the‐art of column stability criteria - Bjorhovde, Reidar (Journal of Civil Engineering and Management, 2010)
The strength and stability of steel columns have been the subjects of a great many studies since the original work of Leonhard Euler in 1744 and 1759. Numerous examinations of elastic buckling of perfectly straight columns were conducted during the 19th century, the most famous being the studies of Engesser and Considère, with several series of column tests attempting to find agreement between theory and physical behavior. The research work continued in the 20th century, examining the influence of material and member imperfections, including the famous tangent modulus work of Shanley, and the resolution of the effects of material non‐linearity, residual stress and column out‐of‐straightness. The definitive solutions were only obtained in the 1970‐s, when modeling and numerical solutions allowed for the incorporation of all nonlinear effects. Since that time reliability and probabilistic solutions have provided state‐of‐the‐art criteria for limit state treatment of the column problem. These principles are now the bases of the design standards for columns in all of the countries in the world. The paper focuses on the major evolutions that have taken place, but especially the work over the past 40 years. Realistic treatment and representation of the strength of columns in actual structures have now been achieved by the engineering profession. First Published Online: 24 Jun 2011